2017
DOI: 10.3389/fphys.2017.00793
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Temporo-Spatial, Mineralogic, Spectroscopic, and Proteomic Analysis of Postnatal Enamel Development in Teeth with Limited Growth

Abstract: Tooth amelogenesis is a complex process beginning with enamel organ cell differentiation and enamel matrix secretion, transitioning through changes in ameloblast polarity, cytoskeletal, and matrix organization, that affects crucial biomineralization events such as mineral nucleation, enamel crystal growth, and enamel prism organization. Here we have harvested the enamel organ including the pliable enamel matrix of postnatal first mandibular mouse molars during the first 8 days of tooth enamel development to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 99 publications
5
9
0
Order By: Relevance
“…The spatial distributions of AMELX, AMBN, ENAM, MMP20, and KLK4 (Figures 1D, 4) agree very well with published data on abundance patterns during specific stages of enamel formation (see Moradian-Oldak, 2012; Bartlett, 2013; Lacruz et al, 2017 and references therein). Our findings are consistent with the number and identifications of proteins of recently published proteomics analyses of pooled human and rodent enamel (Chen et al, 1995; Hubbard and Kon, 2002; Jagr et al, 2012, 2014; Eckhardt et al, 2014; Charone et al, 2016; Pandya et al, 2017; De Lima Leite et al, 2018; Mann et al, 2018; Zhang et al, 2018). For instance, we mapped 19 of the 24 proteins recently reported in enamel onto enamel formation stages (Pandya et al, 2017), and localized close homologs for the remaining five proteins (Supplementary Table 1).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The spatial distributions of AMELX, AMBN, ENAM, MMP20, and KLK4 (Figures 1D, 4) agree very well with published data on abundance patterns during specific stages of enamel formation (see Moradian-Oldak, 2012; Bartlett, 2013; Lacruz et al, 2017 and references therein). Our findings are consistent with the number and identifications of proteins of recently published proteomics analyses of pooled human and rodent enamel (Chen et al, 1995; Hubbard and Kon, 2002; Jagr et al, 2012, 2014; Eckhardt et al, 2014; Charone et al, 2016; Pandya et al, 2017; De Lima Leite et al, 2018; Mann et al, 2018; Zhang et al, 2018). For instance, we mapped 19 of the 24 proteins recently reported in enamel onto enamel formation stages (Pandya et al, 2017), and localized close homologs for the remaining five proteins (Supplementary Table 1).…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are consistent with the number and identifications of proteins of recently published proteomics analyses of pooled human and rodent enamel (Chen et al, 1995; Hubbard and Kon, 2002; Jagr et al, 2012, 2014; Eckhardt et al, 2014; Charone et al, 2016; Pandya et al, 2017; De Lima Leite et al, 2018; Mann et al, 2018; Zhang et al, 2018). For instance, we mapped 19 of the 24 proteins recently reported in enamel onto enamel formation stages (Pandya et al, 2017), and localized close homologs for the remaining five proteins (Supplementary Table 1). Our spatial proteomic data for AMBN, ENAM, MMP20, and CA2 conform nearly identically to the abundances observed through western blotting of successive stages of mouse molar enamel mineralization as reported by Pandya et al (2017).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This approach was leveraged in the use of whole mouse molars. The teeth were harvested at specific and discrete postnatal time points during the first 8 days postnatally, for analyses of their protein composition by western blot and nano LC-MS/MS analysis [ 120 ]. The authors showed how the classic enamel proteins, including ameloblastin, enamelin and Mmp20 decreased one day to the next during tooth development.…”
Section: Animal Models Of Enamel Developmentmentioning
confidence: 99%